2023
DOI: 10.32859/era.26.2.1-23
|View full text |Cite
|
Sign up to set email alerts
|

Ethnogynecological study of traditional therapeutic plants used by the indigenous communities: A case study from District Gujrat Punjab, Pakistan

Salihah Khadim,
Khafsa Malik,
Rahmatullah Qureshi
et al.

Abstract: Background: The present study aimed to evaluate the indigenous knowledge and use of medicinal plant species to treat different gynecological diseases by local people. Indigenous people use medicinal plants to treat various gynecological disorders.Methods: Ethnomedicinal data was collected from 110 randomly selected local informants through semi-structured questionnaires as well as face-to-face interviews. These data was quantitatively analyzed using various ethnobotanical indices such as family importance valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Ethno-gynecological research have been reported by earlier studies from the neighboring areas of country. Khadim et al (2023) Hu et al (2020) and Ahmad et al (2014). The highest value of RFC was recorded for Anethum graveolens, followed by Brassica campestris, Ferula assa-foetida,and Conyza canadensis.…”
Section: Discussionmentioning
confidence: 93%
“…Ethno-gynecological research have been reported by earlier studies from the neighboring areas of country. Khadim et al (2023) Hu et al (2020) and Ahmad et al (2014). The highest value of RFC was recorded for Anethum graveolens, followed by Brassica campestris, Ferula assa-foetida,and Conyza canadensis.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, the focus of the study is specifically on angiosperms, providing comprehensive details on their ethnobotanical significance within the given region (Khadim et al, 2023). This study specifies that people living in the area of Mandi Bahauddin have immense information about uses of plant present in their areas.…”
Section: Resultsmentioning
confidence: 99%